The Virality of Pandemics: Reassembling the Social in the Anthropocene. (January 2021) - Ray, Subhadeepta
Since the outbreak of the severe acute respiratory syndrome (SARS), which was the first pandemic of the twenty-first century, viral epidemics, such as the avian flu, swine flu, Ebola, COVID-19, et cetera, have been appearing with increasing frequency. The adaptation of existing diseases and the emergence of novel viruses are a cause of concern and need to be situated in the context of the anthropogenic events such as deforestation, collapsing biodiversity, species extinction and the melting of polar ice caps. Can the virus make us rethink the categories of life–non-life and classificatory practices of biology? How does the trope of immunity link viral diseases and modern forms of biopower? I attempt to locate the virus as an actor in the evolution of life on the planet that sutures the domains of biological, social, political and the geological. The virus forces us to re-examine our conception of sociality, which is predicated on instituting dichotomies of human–non-human and nature–culture. The reaction to the COVID-19 pandemic may help in overcoming the inertia and helplessness in facing planetary climate crisis.